Нові кургани раннього залізного віку в Пороссі - Ковпаненко, Г.Т.; Бессонова, С.С.; Батуревич, Є.Ю. (Археологія, 1997)
Публікуються матеріали двох поховань скіфського часу (V—IV ст. до н. е.) та одного поховання ранньосарматського часу. В 1982 г. были исследованы несколько курганов на трассе газопровода в Таращанском районе Киевской области. В двух из них обнаружены погребения скифского времени (к. № 1 у с. Петровское конца V — начала IV вв. до н. э. и к. № 1 у с. Лесовичи второй половины IV в. до н. э.) и в одном (Лесовичи, к. № З, погр. 2) — раннезарубинецкого времени. Заслуживают внимания особенности погребального обряда, зафиксированные в курганах скифского времени: сожжение погребенных в наземном деревянном склепе (с. Петровское), ров и погребение коня в отдельной яме (Лесовичи, к. 1). Several mounds were studied in the Tarashcha district, the Kiev Region, in 1982 on the gas-main line. Interments of the Scythian period were found in two mounds (No. 1 near vil. Petrovskoe, dated the end of the 5th and beginning of the 4th cent. В. C. and No. 1 near vil. Lesovichi, dated the second half of the 4th cent. В. C.). Interments of the early Zarubinets period were found in one mound No. 3, vil. Lesovichi, grave 2. Of interest are peculiarities of the burial rite retained in the Scythiam mounds: cremation of corpses in the overground wooden burial vault (vil. Petrovskoe), a ditch and grave of a horse in a separate pit (vil. Lesovichi, mound No. 1)